Superior Thyroid Artery Arising From the Common Carotid Artery- Potential Source for Unpredicted Intraoperative Bleeding- A Cadaveric Case Report - Balaiya Anitha; Shanthini (Academia Anatomica International, 2019)
Superior thyroid artery usually arises from the anterior surface of external carotid artery as its first branch. Superior thyroid artery forms an important collateral circulation in case of unilateral occlusion of common carotid artery. Due to the close relation with superior thyroid artery, external laryngeal nerve is prone to injury during thyroid surgery. Superior thyroid artery occasionally arises from the bifurcation of common carotid artery or from the common carotid artery. In the present cadaveric case, during the routine neck dissection of the cadaver in department of anatomy, anomalous origin of the left superior thyroid artery was found. It was originating from the left common carotid artery at a distance of 1.8 cm proximal to the bifurcation of common carotid artery. The length of left superior thyroid artery was 3.2 cm. left Inferior thyroid artery was present and no anomaly was found. Right superior and inferior thyroid arteries were present and no variations were found. Knowledge about these variations in the origin of superior thyroid artery is extremely important in head and neck surgeries to prevent inadvertant injury and avoid torrential bleeding.